Religiosity and Attitudes Toward Treatment for Mental Health in the Black Church - Davenport, Alexandria D. (Race and social problems, 2021)
To investigate the relationship between dimensions of religiosity and attitudes toward the professional treatment of mental health among African American church attendees. In 2018, surveys were administered to African American attendees of four churches in northeastern Pennsylvania and central New Jersey (n = 435). The independent variables assessed were three dimensions of religiosity: subjective (perceptions and attitudes), organizational (public displays), and non-organizational (private practices). The Multidimensional Measure of Religious Involvement for African Americans scale assessed each dimension of religiosity. The dependent variable was measured through the 20-item scale, Attitudes Toward Mental Health Treatment Scale. We conducted multivariate linear regression with robust standard errors to adjust for clustering effects by church. Covariates adjusted for in the analysis were age, sex, denomination, education, marital status, depressive symptoms, location, and support. Most participants were aged 50 and older (79.3%). They resided in urban (9.89%), rural (2.3%), or suburban (87.8%) settings. Participants who reported high subjective religiosity endorsed less positive attitudes toward professional mental health treatment in comparison with participants reporting low subjective religiosity (β = − 1.36, 95% confidence interval [− 2.35, − 0.39], p < 0.05). No association was found between organizational or non-organizational religiosity in relation to attitudes toward professional mental health service use. Our findings suggest that greater subjective religiosity may be related to lower engagement in and utilization of professional mental health services among African Americans in the northeastern United States.